Penerapan Aroma Terapi Lavender Terhadap Penurunan Tingkat Nyeri Ibu Bersalin Kala I - Yuandira, Mayang Tri; Dewi, Rusmala; Dewi, Apri Rahma (Bunda Edu-Midwifery Journal (BEMJ), 2021)
Childbirth is a process in which the baby, placenta, and amniotic membranes come out of the mother's uterus, normal delivery occurs at 37 weeks of gestation or more without complications. Labor pain occurs when the uterine muscles contract in an attempt to open the cervix and push the baby's head toward the pelvis. The aim of this study was to determine the level of labor pain during phase 1 using lavender aromatherapy. This research used a case study. The results of the study showed that there were significant results of lavender aromatherapy techniques in mothers during the first phase of active Mrs. S. from severe pain (8) to mild (3) and Mrs. N. severe pain (7) to mild (3). From the research results, it can be concluded that after the lavender aromatherapy technique carried out, the two partisipants could reduce pain in the mother during the active phase of labor